A comparative study of antiarrhytmic of propranolol ("inderal") and lidocaine on the heart - Abdulcholiq Chuseri Abdulcholiq Chuseri (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1973)
keywords: propanolol, arrithmias, lidocaine